MODALS DALAM NOVEL THE SWISS FAMILY ROBINSON OLEH JOHAN RUDOLF WYSS - MUTTER, MARIANA EZRA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT In English there are two subclasses of verb; those are lexical verb and auxiliary verb. Modals are a class of auxiliary verb that are combined with the base form to make verb phrase with wide meaning. This study is an attempt to describe and analyze modals in the novel â€œThe Swiss Family Robinsonâ€ by Johan Rudolf Wyss. The aim of this research is to identify and classify the form and meaning ofÂ  modals. The method which is used in this research is descriptive method. The data of modals have been taken from the sentences in the novel â€œThe Swiss Family Robinsonâ€ and have been analyzed by using Quirk et.al. and Frankâ€™s concepts. The result of this study shows that modal forms which are used namely will, shall, can, may, must, would, should, could, might, ought to, have to, be able to, and need, whereas dare is not found in the novel. The study can be continually done by analyzing modals in other literary works. Â  Keywords : Modals, Novel The Swiss Family Robinson